The Utilization of the Tiffani Application As An Alternative Medium In English Vocabulary Learning: Students Perspectives Institute Prima Bangsa Cirebon - Sefiyanti Nur Rizki; Muhammad Kaisal Ababil; Kayla Rizkiana; Cici Situmorang (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Digital transformation has triggered a surge in the adoption of mobile platforms as a means to support English language education, particularly to enhance vocabulary mastery. One of the applications used for vocabulary learning is English with Tiffani. This study aims to evaluate the use of the English with Tiffani application as an alternative in English vocabulary learning based on the perspectives of students at the Prima Bangsa Institute in Cirebon. This research employs a qualitative method, with data obtained through open interviews with students who utilize the application in their learning. The data is analyzed descriptively through the grouping of main themes that emerge from the interviews. The findings of this study indicate that the English with Tiffani application provides a positive learning experience, enhancing students' motivation, engagement, and understanding of English vocabulary. The visual, audio, and game elements are considered to have the potential to create a more interactive and flexible learning atmosphere. However, the results of this research also indicate some issues, one of which relates to difficulties in the login process, audio speed, and the absence of an Indonesian language option that can affect user comfort, especially for beginners. Overall, the English with Tiffani application shows great potential as an alternative medium for learning English vocabulary among college students.